Semantics Analysis of Sentence, Utterance, and Proposition in Blyton’s on the Farm - Helmy Septian Permana; Nabilla Azahra Fitrina; Nurlaila Safitri; Putra Adjie Wicaksono; Hilma Safitri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Explore the differences and relationships between sentences, utterances, and propositions within children’s literature by analyzing On the Farm by Enid Blyton from the Farm Series Collection (Egmont UK Limited, 2014). We use semantic analysis to examine how these linguistic constructions function in narrative discourse. Sentences are analyzed for their structural and descriptive roles, particularly in introducing characters, settings, and actions. Utterances are identified as spoken or written expressions in dialogue that reveal characters’ emotional reactions, questions, and exclamations. Propositions are statements conveying factual or verifiable information, regardless of their truth value. Through close reading of selected passages, we demonstrate that Blyton's text employs sentences to establish narrative coherence, utterances to convey the voices and emotions of characters, and propositions to provide information or opinions. This nuanced understanding of these linguistic units enriches the interpretation of both the form and content of children's stories. Moreover, these insights offer valuable contributions to teaching and semantic studies in the field of literature.